MODERN OCCUPATION AND MEANS OF ITS SUCCESSFUL IMPLEMENTATION - Khodjaeva, Mahliyo (Журнал иностранных языков и лингвистики, 2021)
This article deals with interactiveteaching methods, innovation, cooperative learning, problem situations, andcommunication activities.